Development of an Innovative Blue Economy Model with a Quadruple Helix Approach: Integration of AD-AS Dynamics in Bone Regency - Sandi, Sandi; Inanna, Inanna; Rahmatullah, Rahmatullah; Suradi, Adam Rahman (Quantitative Economics and Management Studies, 2025)
This study formulates an innovative model for blue economy development in Bone Regency by integrating aggregate demand (AD) and aggregate supply (AS) dynamics within a quadruple helix collaboration framework. Quantitative data were obtained from a survey of 100 respondents including fishermen, fish farmers, fishery product processors, and local consumers; qualitative data were collected through in-depth interviews with 12 key informants from the local government, academics, business actors, and coastal communities. Descriptive and thematic analyses indicate that AD is primarily driven by high domestic consumption, but weak in investment, logistics infrastructure, and export market access. On the AS side, marine resource availability is relatively adequate, but productivity, post-harvest quality, and distribution efficiency are constrained by low technology adoption, seasonal production capacity, and long supply chains. Key findings confirm that aligning AD AS requires interventions in product, technology, distribution, and market innovation facilitated by the government through regulations, infrastructure, financing, and human resource development, and strengthened by the roles of academics, industry, and the community. The resulting conceptual model provides a measurable framework for accelerating the development of an inclusive and sustainable blue economy in Bone Regency. This model positions the government as an enabler, academics as providers of research and mentoring, industry as offtakers and investors, and the community as guardians of socio-ecological compliance so that the innovation process runs consistently.